2012
DOI: 10.1016/j.envint.2011.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene expression and a functional analysis of PCB-exposed children: Understanding disease and disorder development

Abstract: The goal of the present study is to understand the probable molecular mechanism of toxicities and the associated pathways related to observed pathophysiology in high PCB-exposed populations. We have performed a microarray-based differential gene expression analysis of children (mean age 46.1 months) of Central European descent from Slovak Republic in a well-defined study cohort. The subset of children having high blood PCB concentrations (>75 percentile) were compared against their low PCB counterparts (<25 pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
33
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 98 publications
7
33
1
Order By: Relevance
“…While the above approach has provided a great deal of evidence regarding the deleterious effects of environmental pollution such as those associated with accidental or occupational contamination by lead, arsenic, or mercury (i.e., the effects of pollutants from point sources) [12,13], it has not proved as effective in studies investigating the effects of low concentrations of persistent organic pollutants such as polychlorinated biphenyls (PCBs) and dioxins (i.e., the effects of pollutants from nonpoint sources), which are frequently found among ordinary citizens, although some studies have suggested that exposure to the latter pollutants is associated with the risk of particular diseases [14,15]. This is because the health effects of environmental pollutants represent the end result of complex interactions between toxic chemicals and the physiological condition of vulnerable tissues, which is influenced by both the genetic background of the affected individual and their lifestyle, e.g., their diet and home environment [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…While the above approach has provided a great deal of evidence regarding the deleterious effects of environmental pollution such as those associated with accidental or occupational contamination by lead, arsenic, or mercury (i.e., the effects of pollutants from point sources) [12,13], it has not proved as effective in studies investigating the effects of low concentrations of persistent organic pollutants such as polychlorinated biphenyls (PCBs) and dioxins (i.e., the effects of pollutants from nonpoint sources), which are frequently found among ordinary citizens, although some studies have suggested that exposure to the latter pollutants is associated with the risk of particular diseases [14,15]. This is because the health effects of environmental pollutants represent the end result of complex interactions between toxic chemicals and the physiological condition of vulnerable tissues, which is influenced by both the genetic background of the affected individual and their lifestyle, e.g., their diet and home environment [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, epidemiologic studies have relied on blood or tissue specimens sampled from a lifetime of a high or low exposure to PCBs and their effects on gene expression profiling. As a result, children with high blood PCB concentrations have shown differential gene expression related to cell-to-cell signaling and interactions, cellular movement, cell signaling, molecular transport, and vitamin and mineral metabolism (Dutta et al, 2012). Wens et al (2011) assessed gene expression changes in human peripheral blood mononuclear cells after in vitro incubation with PCB 126 and individual NDL-PCB congeners (PCB 52,138,and 180).…”
Section: Discussionmentioning
confidence: 99%
“…However, some previous studies have detected associations between the risk of various conditions and exposure to such pollutants and the risk [10,11]. The main reason for this is that the health effects of environmental pollutants represent the final consequences of complex interactions between toxic chemicals and the physiological status of the affected tissue, which is influenced by genetic and lifestyle (e.g., the subject's diet and home environment) factors [12,13].…”
Section: Introductionmentioning
confidence: 94%